2013
DOI: 10.1002/jsfa.6177
|View full text |Cite
|
Sign up to set email alerts
|

Maximising umami taste in meat using natural ingredients: effects on chemistry, sensory perception and hedonic liking in young and old consumers

Abstract: The addition of natural umami-containing ingredients during the cooking of meat can provide enhanced umami and salty taste characteristics. This can lead to increased liking by some consumers, particularly those with raised taste detection thresholds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 40 publications
6
43
0
Order By: Relevance
“…2d revealed a similar pattern to that found in the taste graph, where the flavor was mostly affected by the SP. Panelists preferred the flavor of nuggets containing 2-3 % SP, in consonance with many studies that revealed the pleasantness and fullness of savoury flavors were increased by umami taste (Dermiki et al 2013). However, nugget scored lower when high SP levels ([3 %) were used, possibly a high amount of SP interfered meaty flavor of the nuggets (Chun et al 2005).…”
Section: Flavorsupporting
confidence: 81%
See 1 more Smart Citation
“…2d revealed a similar pattern to that found in the taste graph, where the flavor was mostly affected by the SP. Panelists preferred the flavor of nuggets containing 2-3 % SP, in consonance with many studies that revealed the pleasantness and fullness of savoury flavors were increased by umami taste (Dermiki et al 2013). However, nugget scored lower when high SP levels ([3 %) were used, possibly a high amount of SP interfered meaty flavor of the nuggets (Chun et al 2005).…”
Section: Flavorsupporting
confidence: 81%
“…This is because shiitake mushrooms are high in the non-essential amino acids; glutamic and aspartic acids, and the 5 0 -nucleotides, especially 5 0 -guanosine monophosphate (5 0 -GMP), which were recognized as umami taste compounds (Tseng et al 2011). Dermiki et al (2013) showed the enhanced umami and salty characteristics in cooked meat products added with natural umami-containing ingredients such as yeast extract, shiitake extract, low-salt soy sauce and beef stock paste. They concluded that the synergistic effects of glutamic acid and 5 0 -nucleotides, stimulated by the heat treatment, led to enhance the perception of taste and savoury flavor attributes in the cooked products.…”
Section: Colormentioning
confidence: 99%
“…However, trained panels have been shown to rate cross-modal enhancement and suppression of flavour. For example, where food ingredients high in umami taste compounds were used to enhance umami taste within a complex meat product at constant sodium content, salty taste and beeflike flavour attributes were found by the trained QDA panel to be enhanced in addition to the perceived increase in umami taste (Dermiki et al, 2013). However, another study noted that an untrained, naïve panel was more suitable to demonstrate multisensory saltiness enhancement due to their synthetic attention compared to a trained descriptive panel (Batenburg and van der Velden, 2011).…”
Section: Descriptive Sensory Profiling Methodsmentioning
confidence: 99%
“…Another study on the formulation of fermented sausages with two levels of substitution of sodium chloride by potassium chloride in combination with MSG, disodium inosinate and disodium guanylate along with amino acids like lysine and taurine was reported. The investigators reported that, the replacement of sodium chloride with potassium chloride along with flavour enhancers to the extent of 50% resulted in a product having desirable physico chemical and sensory qualities [25].…”
Section: Sensory Response For Products With Mixture Of Spicementioning
confidence: 99%